2015
DOI: 10.1093/aobpla/plw066
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the drivers of seedling leaf gas exchange responses to warming and altered precipitation: indirect and direct effects

Abstract: Climate change is expected to bring warmer temperatures and more variable precipitation patterns worldwide, patterns that will depend on the ability of the world's flora to take up carbon under these new conditions. We subjected deciduous tree seedlings growing in an old-field ecosystem in Massachusetts, USA to warming and altered precipitation. We found that leaf carbon uptake was greatest under the coolest, wettest conditions, an effect driven by increased soil water availability in these plots. Our findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 68 publications
1
10
0
Order By: Relevance
“…The tree seedlings in this study were grown within a high-light, old-field ecosystem, thereby simulating early secondary successional dynamics. Previous studies at this same experimental field site have found that the precipitation treatments altered heterotrophic soil respiration ( Suseela et al 2012 ), herbaceous plant water use efficiency ( Rodgers et al 2012 ) and tree seedling photosynthesis rates ( Smith et al 2016 ). In contrast, warming has had more limited direct effects, in part because of process acclimation.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…The tree seedlings in this study were grown within a high-light, old-field ecosystem, thereby simulating early secondary successional dynamics. Previous studies at this same experimental field site have found that the precipitation treatments altered heterotrophic soil respiration ( Suseela et al 2012 ), herbaceous plant water use efficiency ( Rodgers et al 2012 ) and tree seedling photosynthesis rates ( Smith et al 2016 ). In contrast, warming has had more limited direct effects, in part because of process acclimation.…”
Section: Introductionmentioning
confidence: 89%
“…Within each of the 36 split-plots, soil moisture was monitored weekly as relative extractable water ( θ R ) using pairs of time-domain reflectometry (TDR) waveguides installed vertically to provide integrated measures of volumetric soil moisture in the top 10 cm and top 30 cm; calculations in Vicca et al (2012) and Smith et al (2016) . Soil temperature was monitored using custom-made linear temperature sensors placed at 2 and 10 cm below the soil surface.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shorter-term changes in temperature (approximately days to weeks) also affect leaf respiration; as with adaptation, this acclimation response tends to slow temperature-standardized respiration after warmer periods of time . Respiration may also accelerate or slow under water stress as a result of an increase in maintenance demand or decrease in growth demand, respectively (Wright et al 2006, Smith et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…While realized responses to climate change will be strongly influenced by other extrinsic factors, such as water (Smith, Pold, Goranson, & Dukes, 2016), nutrient limitations (Sigurdsson, Medhurst, Wallin, Eggertsson, & Linder, 2013), photosynthetic acclimation to CO 2 (Ainsworth & Long, 2005), and disturbances (Randerson et al, 2006), we focus here on the effects of temperature and CO 2 alone, providing a best-case scenario for boreal stand responses to climate change in the absence of these limitations. We hypothesized that: (a) modelled net C-gain would be stimulated by both warming and combined warming and elevated CO 2 in boreal trees species across a broad range of seasonal tem-…”
mentioning
confidence: 99%